(untitled) (PerCursos, 2024)
This article aims to analyze the work of the Brazilian band Gangrena Gasosa, focusing on their 2018 album Gente Ruim Só Manda Lembrança Pra Quem Não Presta, interpreting it as an example of cultural hybridity from which pedagogical insights emerge. The analysis is grounded in Cultural Studies, drawing methodologically from cultural and discourse analysis. Through this examination, the band’s work is presented as a rich cultural artifact, showcasing the fusion of distinct cultural and conceptual elements to create something new, termed Saravá Metal. This genre merges Metal music with Brazilian culture and religiosity, particularly with Afro-Brazilian religious traditions. Furthermore, the band navigates serious themes while often employing humor, further demonstrating the hybridity present in their work. In addition to being an example of cultural hybridity, Gangrena Gasosa’s work contributes significantly to discussions surrounding Afro-Brazilian religions, offering a counter-narrative to prevalent prejudice and denial by fostering understanding and normalization of these traditions.